Injection molded body and method for producing same, method for producing composite fiber, carbon nanotube-attached carbon fiber and method for producing same, and method for producing carbon fiber composite material
By forming a curved carbon nanotube structure on the carbon fiber surface of the injection molded body and crosslinking it, combined with post-curing treatment, the problem of insufficient mechanical strength of the existing injection molded body is solved, and higher mechanical strength and interface bonding strength are achieved.
Patent Information
- Application Number
- CN202380053365.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-05-12
- Publication Date
- 2025-03-11
AI Technical Summary
In the existing injection molded bodies, although the fiber volume content of carbon fiber has been increased, the improvement of mechanical strength is limited, making it difficult to meet the demand for higher mechanical strength.
The structure consisting of a plurality of carbon nanotubes in a curved shape is formed on the surface of the carbon fiber, and the carbon nanotubes are cross-linked with each other using a sizing agent to form composite fibers. The composite fiber is embedded in the thermoplastic resin, and the mechanical strength is further improved by post-curing treatment.
The mechanical strength of the injection molded body is significantly improved, the interfacial bonding strength between the composite fiber and the matrix resin is enhanced, and the risk of disintegration and peeling of the structure is reduced.
Smart Images

Figure CN119604563A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an injection molded body and a method for producing the same, a method for producing a composite fiber, a CNT-attached carbon fiber and a method for producing the same, and a method for producing a carbon fiber composite material. Background Art
[0002] Injection molded products are suitable for mass production because they are formed by injecting molten thermoplastic resin into a metal mold. Injection molded products are known in which the mechanical strength is improved by making the matrix resin formed of thermoplastic resin contain reinforcing fibers. For example, Patent Document 1 discloses that the mechanical strength of a gear tooth is improved by injection molding in a manner in which fibers are oriented along the tooth tip.
[0003] On the other hand, a composite fiber (composite material) is known, which has a carbon fiber and a structure composed of a plurality of carbon nanotubes (hereinafter referred to as CNT) attached to the surface of the carbon fiber (for example, refer to Patent Document 2). The structure of the composite fiber forms a network structure in which a plurality of CNTs are connected to each other and attached to the surface of the carbon fiber. The structure of Patent Document 2 increases its thickness by using curved CNTs. Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Laid-Open No. 2008-008404 Patent Document 2: International Publication No. 2019 / 240094 Summary of the invention Problems to be solved by the invention
[0005] Although the mechanical strength of the injection molded article containing the reinforcing fibers as described above is improved to a certain extent, it is desired to have a higher mechanical strength. However, even if the fiber volume content of the carbon fibers in the injection molded article is increased, a significant improvement in the mechanical strength cannot be obtained.
[0006] An object of the present invention is to provide an injection molded body and a method for producing the same, a method for producing a composite fiber, a CNT-attached carbon fiber and a method for producing the same, and a method for producing a carbon fiber composite material that can further improve the mechanical strength. Means for solving problems
[0007] The injection molded body of the present invention includes multiple composite fibers and a matrix resin, wherein the multiple composite fibers have carbon fibers, a structure and a sizing agent, wherein the structure is composed of multiple carbon nanotubes with a curved shape having a curved portion, forming a network structure having a contact portion where the carbon nanotubes are in direct contact with each other, the structure is arranged on the surface of the carbon fibers, the sizing agent is arranged at least around the contact portion, and the carbon nanotubes in direct contact are cross-linked with each other through a structure obtained by reaction with functional groups of the carbon nanotubes; the matrix resin embeds the multiple composite fibers and is formed by a thermoplastic resin.
[0008] The method for manufacturing an injection molded body of the present invention comprises a kneading step of kneading a composite fiber and a thermoplastic resin and an injection step of obtaining an injection molded body in which the composite fiber is embedded with a matrix resin formed by the thermoplastic resin by injection molding the thermoplastic resin containing the composite fiber, wherein the composite fiber comprises a carbon fiber, a structure and a sizing agent, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion, forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other, the structure is arranged on the surface of the carbon fiber, the sizing agent is arranged at least around the contact portion, and the carbon nanotubes in direct contact are cross-linked with each other via a structure obtained by reaction with functional groups of the carbon nanotubes.
[0009] The method for manufacturing composite fibers of the present invention comprises a structure forming step and a post-curing step, wherein in the structure forming step, a structure is formed on the surface of the carbon fiber, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion, and forms a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other; in the sizing treatment step, the carbon fiber forming the structure is brought into contact with a sizing treatment liquid, and the sizing agent is imparted to obtain a composite fiber, wherein the sizing treatment liquid dissolves the raw material of the sizing agent that cross-links the carbon nanotubes in direct contact with each other; and in the post-curing step, the sizing agent of the composite fiber is post-cured.
[0010] The CNT-attached carbon fiber of the present invention is a product obtained by removing the resin in a composite in which carbon fiber and resin are integrated. A structure is provided on the surface of the carbon fiber, and the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion, forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other.
[0011] The manufacturing method of CNT-attached carbon fiber of the present invention comprises a preparation step and a removal step. In the preparation step, a composite of carbon fiber having a structure provided on the surface and a resin is prepared as a whole, wherein the structure is composed of a plurality of carbon nanotubes in a curved shape having a curved portion and forms a network structure having contact portions in which the carbon nanotubes are in direct contact with each other; in the removal step, the resin of the composite is removed to obtain the CNT-attached carbon fiber.
[0012] The manufacturing method of the carbon fiber composite material of the present invention comprises a preparation step, a removal step and a composite material production step. In the preparation step, a composite material in which carbon fiber having a structure provided on the surface and a resin are integrated is prepared, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion and forms a network structure having contact portions in which the carbon nanotubes are in direct contact with each other; in the removal step, the resin of the composite material is removed to obtain CNT-attached carbon fiber; in the composite material production step, the CNT-attached carbon fiber is embedded in a matrix resin to obtain a carbon fiber composite material. Effects of the Invention
[0013] According to the present invention, as the reinforcing fiber of the injection molded body, a composite fiber is used in which a structure composed of a plurality of carbon nanotubes in a curved shape is formed on the surface of the carbon fiber and a sizing agent is applied to crosslink the carbon nanotubes in direct contact with each other in the structure, so that the mechanical strength of the injection molded body can be further improved. In addition, by post-curing the sizing agent, the mechanical strength of the injection molded body can be further improved.
[0014] Furthermore, according to the present invention, the product obtained by removing the resin from the composite containing the carbon fibers having the structure provided on the surface can be easily recycled as the CNT-attached carbon fibers to, for example, improve the mechanical strength of the molded body. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is an explanatory diagram schematically showing a molded body according to an embodiment. Figure 2 It is an explanatory diagram showing a composite fiber. Figure 3 It is an explanatory diagram showing the adhesion state of the sizing agent to the CNT. Figure 4 It is an explanatory diagram showing the adhesion state of the sizing agent in the contact portion where CNTs are in contact with each other. Figure 5 It is an explanatory diagram showing another adhesion state of the sizing agent to the CNT. Figure 6 It is an explanatory diagram showing another adhesion state of the sizing agent in the contact portion where CNTs are in contact with each other. Figure 7 It is an explanatory diagram schematically showing the steps of producing a molded body. Figure 8 It is an explanatory diagram showing the structure of an attachment device for attaching CNTs to carbon fibers and the passing position of carbon fibers in a dispersion liquid. Fig. 9 This is a graph showing the relationship between the post-curing temperature and the post-curing period in the post-curing of the sizing agent. Fig.10 This is a flowchart showing an example of the steps of producing a carbon fiber composite material using CNT-attached carbon fibers recovered from a processed product. Fig.11 This is a SEM photograph showing the bending state of the CNT material used in the examples. Fig.12 This is a graph showing the tensile strength of the test piece of Example 2. Fig.13 This is a graph showing the maximum load of Example 2. Fig.14 This is a diagram showing the displacement of the test piece at the maximum load of Example 2. Fig.15 This is a graph showing the tensile strength of the test piece of Example 3. Fig.16 This is a diagram showing the displacement of the test piece at the maximum load of Example 3. Fig.17 This is a SEM image showing a fracture surface of the test piece of Example 3. Fig.18 This is a SEM image showing a fracture surface of the test piece of Comparative Example 2. Fig.19 This is a FE-SEM image showing the state of the composite fiber after the matrix resin of the test piece was removed by burning. DETAILED DESCRIPTION
[0016] [Molding body] like Figure 1 As shown in FIG. 1 , the molded body 10 is formed by embedding the composite fiber 11 as a reinforcing fiber in a matrix resin M formed of a thermoplastic resin. The molded body 10 is an injection molded body made by injection molding. Figure 1 In the figure, for the sake of convenience, the molded body 10 is depicted in a rectangular parallelepiped shape, but the shape of the molded body 10 may be any shape.
[0017] The matrix resin M is not limited as long as it is a known thermoplastic resin that can be injection molded. The thermoplastic resin may also contain additives. Examples of thermoplastic resins include general-purpose resins such as polyolefins (polyethylene, polypropylene, etc.), polyvinyl chloride, polystyrene, acrylonitrile / styrene (AS) resins, acrylonitrile / butadiene / styrene (ABS) resins, methacrylic resins (PMMA, etc.), thermoplastic epoxy resins, engineering plastics such as polyamide, polyacetal, polyester (polyethylene terephthalate, etc.), ultra-high molecular weight polyethylene, polycarbonate, phenoxy resins, and super engineering plastics such as polyphenylene sulfide, polyetheretherketone, polyetherketoneketone, liquid crystal polymers, polytetrafluoroethylene, polyetherimide, polyarylate, and polyimide.
[0018] [Composite Fiber] Figure 2 1 shows a composite fiber bundle 12 used in making the molded body 10. The composite fiber bundle 12 is obtained by bundling a plurality of composite fibers 11. Each composite fiber 11 has a carbon fiber 13 and a structure 14 formed on its surface, and a sizing agent 15 is applied to the structure 14 (see Figure 3 The structure 14 is a structure formed by a plurality of carbon nanotubes (hereinafter referred to as CNTs) 17 intertwined with each other.
[0019] The composite fiber bundle 12 is composed of, for example, 12,000 composite fibers 11. The number of composite fibers 11 constituting the composite fiber bundle 12 is not particularly limited, and may be, for example, in the range of 10,000 to 100,000. Figure 1 In FIG. 1 , for the convenience of illustration, a plurality of composite fibers 11 are depicted.
[0020] The carbon fiber bundle formed by bundling the original fiber, that is, the carbon fiber 13, used when making the composite fiber 11, is preferably a bundle in which the carbon fibers 13 are not substantially interwoven with each other, or are less interwoven. Such a carbon fiber bundle makes it easy to evenly open the carbon fibers 13 and evenly attach the CNT 17 to each carbon fiber 13. The carbon fiber 13 is not particularly limited, and can be a PAN-based carbon fiber, a pitch-based carbon fiber obtained by burning organic fibers derived from petroleum, coal, and coal tar, such as polyacrylonitrile, rayon, asphalt, and organic fibers derived from wood or plant fibers can be used. Carbon fibers obtained by burning, etc., can also be commercially available carbon fibers. In addition, the diameter and length of the carbon fiber 13 are not particularly limited. The carbon fiber 13 can preferably use a carbon fiber whose diameter is in the range of about 5 μm or more and 20 μm or less, and more preferably use a carbon fiber in the range of 5 μm or more and 10 μm or less. The carbon fiber 13 can preferably use a slender carbon fiber, and its length is preferably 50 m or more, more preferably in the range of 100 m or more and 100000 m or less, and further preferably in the range of 100 m or more and 10000 m or less. In addition, in the molded body 10, the carbon fibers 13 may be cut into shorter lengths.
[0021] As described later, curved CNTs 17 are used as CNTs 17 constituting the structure 14. Thus, compared with the case of using CNTs with high linearity, a greater number of CNTs 17 are attached to the carbon fibers 13, the thickness of the structure 14 is greater, and the CNTs 17 are woven like fibers of a nonwoven fabric.
[0022] The CNTs 17 constituting the structure 14 are uniformly dispersed and interwoven with each other in the substantially entire surface of the carbon fiber 13, thereby forming a network structure in which a plurality of CNTs 17 are connected in an interwoven state. The connection mentioned here includes physical connection (simple contact) and chemical connection. The CNTs 17 are in direct contact with each other, and there are no inclusions such as dispersants such as surfactants or adhesives between them.
[0023] A portion of CNT17 constituting the structure 14 is directly attached and fixed on the surface of the carbon fiber 13. Thus, the structure 14 is directly attached to the surface of the carbon fiber 13. The direct attachment of CNT17 to the surface of the carbon fiber 13 means that there is no dispersant such as a surfactant or an adhesive between the CNT17 and the surface of the carbon fiber 13, and the CNT17 is directly attached to the carbon fiber 13, and its attachment (fixation) is bonded by van der Waals force. By directly attaching a portion of CNT17 constituting the structure 14 to the surface of the carbon fiber 13, there is no need for a dispersant or an adhesive, and the structure 14 is in direct contact with the surface of the carbon fiber 13.
[0024] In addition, among the CNTs 17 constituting the structure 14, some are not in direct contact with the surface of the carbon fiber 13, but are fixed to the carbon fiber 13 by interweaving with other CNTs 17. In addition, some CNTs 17 are directly attached to the surface of the carbon fiber 13 and are fixed to the carbon fiber 13 by interweaving with other CNTs 17. In the following description, the fixation of CNTs 17 to these carbon fibers 13 is collectively referred to as attachment to the carbon fiber 13. In addition, the state in which CNTs 17 are entangled or interwoven with each other includes the state in which a part of CNTs 17 is pushed against other CNTs 17.
[0025] In addition to the CNTs 17 directly attached to the surface of the carbon fiber 13 as described above, the CNTs 17 constituting the structure 14 also include CNTs 17 that are not in direct contact with the surface of the carbon fiber 13 but are fixed to the carbon fiber 13 by interweaving with other CNTs 17. Therefore, compared with the case where the structure of the conventional composite fiber is composed only of CNTs directly attached to the surface of the carbon fiber, the structure 14 is composed of more CNTs 17. That is, the number of CNTs 17 attached to the carbon fiber 13 is greater than the number of CNTs attached to the carbon fiber in the conventional structure.
[0026] As described above, since CNT17 is not attached to the surface of carbon fiber 13 via inclusions, CNT17 constituting structure 14 is not easily peeled off from the surface of carbon fiber 13. In molded body 10, CNT17 enters the voids of complexly interwoven structure 14, and matrix resin M is solidified, so composite fiber 11 is firmly bonded to matrix resin M through anchoring effect (mechanical bonding). The voids of structure 14 are openings exposed on its surface and hollow spaces formed inside structure 14. In addition, structure 14 is a structure with a large thickness and CNT17 is woven like nonwoven fabric. The elastic modulus of the composite area obtained by solidification of matrix resin M entering into structure 14 is higher than matrix resin M and lower than carbon fiber 13. By such a change in elastic modulus, stress concentration around carbon fiber 13 is alleviated. The composite fiber 11 makes it difficult for the carbon fibers 13 or the composite fiber 11 to separate from the matrix resin M due to the above-mentioned anchoring effect and relaxation of stress concentration, and as a result, the mechanical strength such as tensile strength of the molded body 10 is improved.
[0027] In addition, the properties of the molded body 10 improved by attaching CNT 17 to the surface of the carbon fiber 13 and forming a non-woven fabric-like structure 14 with a relatively large thickness include, in addition to tensile strength, elastic modulus, vibration attenuation characteristics (vibration damping), durability against repeated bending, etc.
[0028] The structures 14 of each composite fiber 11 of the composite fiber bundle 12 are independent structures, and the structure 14 of one composite fiber 11 and the structure 14 of another composite fiber 11 do not share the same CNT 17. In other words, the CNT 17 included in the structure 14 provided on one carbon fiber 13 is not included in the structure 14 provided on other carbon fibers 13.
[0029] like Figure 3 As shown, the sizing agent 15 is applied to CNT17 in a state of coating the contact portions where CNT17 are in direct contact with each other. In this example, the sizing agent 15 has a carbodiimide-derived structure, and the carbodiimide is generated by the reaction of functional groups present on the surface of CNT17, such as hydrophilic groups such as hydroxyl (-OH) and carboxyl (-COOH), with the carbodiimide group (-N=C=N-) of the carbodiimide compound. That is, the sizing agent 15 cross-links the CNT17 in direct contact with each other via the carbodiimide-derived structure. As a result, CNT17 are fixed to each other through their contact portions where they are in direct contact with each other and the sizing agent 15. As shown Figure 4 As shown, CNTs 17 at the contact portion are in direct contact with each other, and around the contact portion where the surfaces of each CNT 17 are close to each other, CNTs 17 are cross-linked by sizing agent 15 .
[0030] There is no particular limitation on the method of imparting functional groups to the surface of CNT17, and the functional groups can be imparted by various treatments performed after the production of CNT17, or by a functional group imparting treatment. The functional group imparting treatment can be, for example, a wet anodic electrolytic oxidation method or an ozone oxidation method. When the sizing agent 15 is imparted to the structure 14, as long as the surface of CNT17 has functional groups, there is no particular limitation on the timing of imparting functional groups to the surface of CNT17.
[0031] The carbodiimide compound is a compound containing two or more structures represented by formula (1) where n is an integer of 1 or more. R is, for example, a hydrocarbon. Examples of the hydrocarbon include aliphatic hydrocarbons, alicyclic hydrocarbons, and aromatic hydrocarbons.
[0032] [Chemical formula 1]
[0033] As the carbodiimide compound, for example, as described in Japanese Patent Publication No. 2007-238753, a carbodiimide compound used as a curing agent for water-based resins can be used, or a commercially available carbodiimide compound can be used. As a commercially available product of the carbodiimide compound, for example, "CARBODILITE V-02" (trade name, manufactured by Nisshinbo Chemical Inc.) can be cited. The carbodiimide compound having a hydrophilic segment acts as an aqueous crosslinking agent that dissolves in water and crosslinks CNT17 with each other.
[0034] As described above, sizing agent 15 serves as a cross-linking agent, and by cross-linking contacting CNTs 17 constituting structure 14 , the adhesion between CNTs 17 is further strengthened, and structure 14 is further difficult to disintegrate.
[0035] In addition, if Figure 3 As shown, the sizing agent 15 is attached to the carbon fiber 13 and the CNT 17 in a state of covering the contact portion of the carbon fiber 13 and the CNT 17 directly in contact therewith. In the same manner as the sizing agent 15 and the CNT 17, the carbon fiber and the CNT 17 are cross-linked by the carbodiimide-derived structure generated by the reaction of the carbodiimide group with the functional groups on the surfaces of the carbon fiber 13 and the CNT 17. In this way, the sizing agent 15 makes the state of the CNT 17 attached to the carbon fiber 13 more firmly by cross-linking the carbon fiber and the CNT 17, making it difficult for the structure 14 to be peeled off from the carbon fiber 13.
[0036] By using the sizing agent 15, in the injection molding machine, during the kneading of the thermoplastic resin mixed with the composite fiber 11 to form the matrix resin M, the peeling and falling off of the structure 14 from the carbon fiber 13 and the total or partial disintegration of the structure 14 can be effectively suppressed. As a result, the interfacial bonding strength between the carbon fiber 13 or the composite fiber 11 and the matrix resin M can be reliably improved, thereby achieving a reliable improvement in the mechanical strength of the molded body 10, and further obtaining uniform preferred characteristics.
[0037] In addition, if CNTs 17 are in direct contact with each other, and CNTs 17 are cross-linked with each other by sizing agent 15 around the contact portion in direct contact, CNTs 17 may be coated with sizing agent 15 as described above, or may be coated with sizing agent 15 as described above. Figure 5 and Figure 6 Similarly, if the carbon fiber 13 and the CNT 17 are in direct contact, and the carbon fiber 13 and the CNT 17 are cross-linked by the sizing agent 15 around the contact portion of the direct contact, then Figure 5 As shown, the sizing agent 15 may not coat the CNT 17 .
[0038] Although the sizing agent 15 of this example has a carbodiimide-derived structure as described above, the sizing agent 15 is not particularly limited as long as it can crosslink the carbon nanotubes in direct contact with each other via the following structure (i.e., a structure obtained by reacting a functional group present on the surface of CNT17 with a functional group of a raw material (compound) of the sizing agent). For example, the sizing agent 15 also preferably has the following structure, i.e., an isocyanate-derived structure generated by reacting a functional group present on the surface of CNT17 with an isocyanate group of an isocyanate compound having two or more isocyanate groups. As shown in this example, the sizing agent 15 having a carbodiimide-derived structure is particularly preferred because it allows CNT17 to be more firmly crosslinked with each other, and carbon fiber 13 and CNT17.
[0039] In addition, in the structure 14, a plurality of CNTs 17 are used to form a void 19 surrounded by them as described above. In order not to hinder the matrix resin M from entering the structure 14, it is preferred that the sizing agent 15 does not block the void 19 as much as possible. In order not to block the void 19, the ratio of the mass of the sizing agent 15 attached to the structure 14 to the mass of the carbon fiber 13, that is, the sizing agent mass ratio Rm, is preferably within a range of 0.6% or more and 1.1% or less.
[0040] Depending on the diameter of the carbon fiber 13, the mass per unit length of the carbon fiber 13 increases or decreases, and the mass of the preferred sizing agent 15 attached to the structure 14 also increases or decreases. However, within the range of the diameter of the carbon fiber 13 generally used as a reinforcing fiber for a molded body, the change in the preferred sizing agent mass ratio Rm relative to the diameter of the carbon fiber 13 is slight, and even for carbon fibers 13 of any diameter, as long as it is within the range of the above-mentioned sizing agent mass ratio Rm, clogging of the voids 19 can be prevented. For carbon fibers 13 with a diameter in the range of 4 μm or more and 8 μm or less, it was confirmed that the voids 19 would not be clogged when the sizing agent mass ratio Rm was 0.6% or more and 1.1% or less. In addition, even if part of the voids 19 in the structure 14 were clogged, there was no problem, and it was confirmed that the composite fiber 11 could be used without any problem when the sizing agent mass ratio Rm was 3% or less.
[0041] The CNT17 attached to the carbon fiber 13 is in a curved shape. The curved shape of the CNT17 is the shape of a curved portion (curved portion) due to the presence of a five-membered ring and a seven-membered ring of carbon in the graphite structure of the CNT17, and can be evaluated as a shape of the CNT17 being bent, bent, etc. by SEM observation. For example, the curved shape of the CNT17 means that there is a curved portion at least one place per average length of the utilization range of the CNT17 described later. Even in the case of being longer, the CNT17 of this curved shape is attached to the surface of the carbon fiber 13 as a curved surface in various postures. In addition, the CNT17 of the curved shape is easy to form a space (gap) between the surface of the carbon fiber 13 to which it is attached or between the attached CNT17, and other CNT17 enters the space. Therefore, by using the CNT17 of the curved shape, compared with the case of using the CNT of a shape with higher linearity, the number of CNT17 attached to the carbon fiber 13 (the number of CNT17 forming the structure 14) becomes larger.
[0042] The length of CNT17 is preferably in the range of 0.1 μm or more and 10 μm or less. If the length of CNT17 is 0.1 μm or more, it is possible to more reliably form a structure 14 in which CNT17 are intertwined and directly contact or directly connected to each other, and it is possible to more reliably form a space for other CNT17 to enter as described above. In addition, if the length of CNT17 is 10 μm or less, CNT17 will not be attached across the carbon fibers 13. That is, as described above, the CNT17 contained in the structure 14 provided on one carbon fiber 13 will not be included in the structure 14 provided on other carbon fibers 13.
[0043] The length of CNT17 is more preferably within the range of 0.2 μm or more and 5 μm or less. If the length of CNT17 is 0.2 μm or more, the number of attached CNT17 can be increased to thicken the structure 14. If the length of CNT17 is 5 μm or less, when CNT17 is attached to the carbon fiber 13, CNT17 is less likely to aggregate and is more likely to be evenly dispersed. As a result, CNT17 is more evenly attached to the carbon fiber 13.
[0044] In addition, CNTs with high linearity or CNTs outside the above-mentioned length range may be mixed as CNTs attached to the carbon fiber 13. Even if mixed, for example, by allowing CNTs with high linearity to enter the space formed by CNT17, the number of CNTs attached to the carbon fiber 13 can be increased.
[0045] The average diameter of CNT17 is preferably in the range of 0.5nm to 30nm, more preferably in the range of 3nm to 10nm. If the diameter of CNT17 is 30nm or less, it is flexible and easy to adhere to the surface of carbon fiber 13. In addition, it is easy to interweave with other CNT17 and fix on carbon fiber 13, so that the formation of structure 14 is more reliable. In addition, if the diameter of CNT17 is 10nm or less, the bonding between CNT17 constituting structure 14 becomes firm. In addition, the diameter of CNT17 is a value measured using a transmission electron microscope (TEM: Transmission Electron Microscope) photograph. CNT17 can be a single layer or a multilayer, but preferably a multilayer.
[0046] The number of CNT17 attached to the carbon fiber 13 can be evaluated by the thickness of the structure 14 (radial length of the carbon fiber 13). The thickness of each part of the structure 14 can be obtained by, for example, sticking a part of the structure 14 on the surface of the carbon fiber 13 to a transparent tape or the like to peel it off, and measuring the cross section of the structure 14 remaining on the surface of the carbon fiber 13 by SEM or the like. In order to roughly evenly cover the measurement range of the specified length of the carbon fiber 13 along the fiber axis direction, the average of the values obtained by measuring the thickness of the structure 14 at 10 points in the measurement range is taken as the thickness of the structure 14. The length of the measurement range is, for example, 5 times the length of the upper limit of the length range of the CNT17 mentioned above.
[0047] The thickness (average) of the structure 14 obtained as described above is within the range of 10 nm to 300 nm, preferably within the range of 15 nm to 200 nm, and more preferably within the range of 50 nm to 200 nm. If the thickness of the structure 14 is 150 nm or less, the impregnation of the resin between the carbon fibers 13 is better.
[0048] In addition, the CNT mass ratio Rc, which is the mass ratio of CNT 17 to the composite fiber 11, can be used to evaluate the adhesion state of CNT 17 to the carbon fiber 13. When the mass of the carbon fiber 13 of a predetermined length (hereinafter referred to as CF mass) is Wa and the mass of CNT 17 attached to the carbon fiber 13 (hereinafter referred to as CNT mass) is Wb, the CNT mass ratio Rc is obtained by "Rc = Wb / (Wa + Wb)".
[0049] CNT17 is preferably uniformly attached to the carbon fiber 13, preferably attached in a manner that covers the surface of the carbon fiber 13. The uniformity of the attachment state of CNT17 relative to the carbon fiber 13 can be observed by SEM, and the obtained image is evaluated by visual inspection. In this case, it is preferred to observe and evaluate multiple parts (for example, 10 parts) in a manner that roughly evenly covers a range of a specified length of the carbon fiber 13 (for example, a range of 1 cm, 10 cm, 1 m) along the fiber axis direction.
[0050] In addition, using the above-mentioned CNT mass ratio Rc, the uniformity of the attachment of CNT17 to the carbon fiber 13 can be evaluated. The CNT mass ratio Rc is preferably 0.001 or more and 0.008 or less. If the CNT mass ratio Rc is 0.001 or more, in the molded body 10, the effect of improving the characteristics by using the structure 14 as described above can be reliably obtained. If the CNT mass ratio Rc is 0.008 or less, the thermoplastic resin forming the matrix resin M reliably enters the voids 19 of the structure 14. In addition, it is more preferred that the CNT mass ratio Rc is 0.002 or more and 0.006 or less. If the CNT mass ratio Rc is 0.002 or more, the structure 14 (CNT17) functions more reliably between almost all the carbon fibers 13. If the CNT mass ratio Rc is 0.006 or less, the matrix resin M reliably enters the structure 14, and even when the ratio of the matrix resin M in the molded body 10 is low, the structure 14 can function more reliably. Furthermore, even when the ratio of the matrix resin M is low, since the CNTs 17 are present at a high concentration in the resin between the carbon fibers, the toughness strength of the molded body 10 can be improved by utilizing the reinforcement effect thereof.
[0051] The standard deviation s of each CNT mass ratio Rc of the 10 measurement locations set within the range of 1m of the length of a composite fiber 11 (hereinafter referred to as the evaluation range) is preferably 0.0005 or less, and more preferably 0.0002 or less. In addition, the standard deviation s is preferably less than 40% relative to the average of the CNT mass ratio Rc, and more preferably less than 15%. The 10 measurement locations are preferably set to cover the evaluation range roughly evenly. The standard deviation s becomes an indicator of the number of attached roots (attached amount) of CNT17 attached to the carbon fiber 13 and the thickness deviation of the structure 14. The smaller the thickness deviation, the smaller the value of the standard deviation s. Therefore, the smaller the standard deviation s, the better. The number of attached roots of CNT17 and the thickness deviation of the structure 14 are manifested as differences in the properties of the composite fiber 11 and the molded body 10 using the composite fiber 11 derived from CNT17. If the standard deviation s is 0.0005 or less, the properties of the composite fiber 11 and the molded body 10 derived from CNT17 can be more reliably exerted, and if it is 0.0002 or less, the properties derived from CNT17 can be fully and reliably exerted. In addition, the standard deviation s is obtained by formula (2). The value n in formula (2) is the number of measurement locations (n = 10 in this example), the value Ri is the CNT mass ratio Rc of the measurement location, and the value Ra is the average value of the CNT mass ratio Rc.
[0052] [Mathematical formula 1]
[0053] [Measurement of CNT mass ratio] About 1 m of the composite fiber bundle 12 (for example, about 12,000 composite fibers 11) is cut out of the measurement site for determining the CNT mass ratio Rc as a measurement sample, and the CNT mass ratio Rc is determined as follows. (1) The measurement sample is placed in a liquid (hereinafter referred to as the measurement liquid) that serves as a dispersion medium for CNT17. As the measurement liquid, a liquid obtained by adding a dispersant to NMP (N-methyl-2-pyrrolidone, CAS registration number: 872-50-4) is used. The dispersant is added to the measurement liquid to prevent CNT17 from reattaching to the carbon fiber 13, but it may not be added. The amount of the measurement liquid is, for example, 100 ml relative to 10 g of the measurement sample. (2) Measure the difference between the mass of the measuring liquid before the measuring sample is added and the mass of the measuring liquid containing the measuring sample after the addition, and use it as the mass of the measuring sample, that is, the sum of the CF mass Wa of the carbon fiber 13 and the CNT mass Wb of the CNT 17 attached to the carbon fiber 13 (Wa+Wb). (3) The measurement liquid containing the measurement sample is heated to completely separate the CNTs 17 attached to the carbon fibers 13 from the carbon fibers 13 and disperse the CNTs 17 in the measurement liquid. (4) Using an absorptiophotometer, measure the absorbance (transmittance) of the test liquid in which CNT17 is dispersed. The concentration of CNT17 in the test liquid (hereinafter referred to as CNT concentration) is calculated from the measurement results of the absorptiophotometer and a pre-made calibration curve. The CNT concentration is the mass percentage concentration given by "C = W2 / (W1+W2)" when its value is set to C, the mass of the test liquid is set to W1, and the mass of CNT17 contained in the test liquid is set to W2. (5) Based on the obtained CNT concentration and the mass of the measurement liquid before the measurement sample is added, the CNT mass Wb of the CNT 17 in the measurement liquid is calculated. (6) Based on the sum (Wa+Wb) of the CF mass Wa and the CNT mass Wb obtained in (2) and the CNT mass (Wb) of CNT 17, the CNT mass ratio Rc (=Wb / (Wa+Wb)) is calculated.
[0054] In the measurement of the above absorbance, a spectrophotometer (for example, SolidSpec-3700, manufactured by Shimadzu Corporation, Japan, etc.) can be used, and as the measurement wavelength, for example, 500 nm can be used. In addition, during the measurement, it is preferred that the measurement liquid is contained in a quartz measurement sample cell. Furthermore, the absorbance of the dispersion medium that does not contain impurities other than the dispersant is measured as a reference, and the concentration C of CNT17 can be calculated using the difference between the absorbance of the measurement liquid in which CNT17 is dispersed and the reference. In addition, in the measurement of the CNT mass ratio Rc, a composite fiber from which the sizing agent 15 is removed from the composite fiber bundle 12 is used. However, when the mass of the sizing agent 15 is about 1 / 100 relative to the mass of the carbon fiber 13, the presence or absence of the sizing agent 15, that is, the mass of the sizing agent 15 will not substantially affect the preferred range of the CNT mass ratio Rc. At this time, the mass of the composite fiber 11 to which the sizing agent 15 is attached can be regarded as the sum of the CF mass Wa and the CNT mass Wb (Wa+Wb).
[0055] When evaluating uniformity based on the CNT mass ratio Rc, 10 measurement locations are set to roughly evenly cover the evaluation range (e.g., length 1 m) of the composite fiber bundle 12 to be evaluated. These 10 measurement locations are the two ends of the evaluation range and the 8 locations in between, and the CNT mass ratio Rc is calculated for each of the measurement locations according to the above-mentioned procedure.
[0056] [Determination of sizing agent mass ratio] In the measurement of the sizing agent mass ratio Rm, three composite fibers 11 are cut out as a measurement sample from a composite fiber bundle 12 in which a sizing agent 15 is attached to a structure 14 of each composite fiber 11, for example, and Rm is determined as follows. The length of the composite fiber 11 cut out as the measurement sample is, for example, 5 m. In addition, the number and length of the composite fibers 11 as the measurement sample are not limited to these examples.
[0057] (1) A measurement sample is added to the measurement solution of CNT 17. The conditions of the measurement solution and the dispersion medium are the same as those in the measurement of the CNT mass ratio Rc described above. (2) Measure the difference between the mass of the measuring liquid before the measuring sample is put in and the mass of the measuring liquid containing the measuring sample after the measurement sample is put in, and use it as the mass of the measuring sample, that is, the sum of the CF mass Wa of the carbon fiber 13, the CNT mass Wb of the CNT17 attached to the carbon fiber 13, and the sizing agent mass Wc of the sizing agent 15 attached to the CNT17 (Wa+Wb+Wc). (3) The measurement liquid containing the measurement sample is heated to completely separate the CNTs 17 attached to the carbon fibers 13 and disperse the CNTs 17 in the measurement liquid. (4) As in the case of measuring the CNT mass ratio Rc, the absorbance of the measurement liquid in which the CNTs 17 are dispersed is measured using an absorptiophotometer, and the CNT concentration of the CNTs 17 in the measurement liquid is calculated based on the absorbance and a pre-made calibration curve. The CNT mass Wb in the measurement liquid is calculated based on the obtained CNT concentration and the mass of the measurement liquid before the measurement sample is added. (5) The CF mass Wa is determined based on the catalog value of the carbon fiber 13 (raw yarn) used. (6) The difference obtained by subtracting the CF mass Wa obtained in (5) and the CNT mass Wb obtained in (4) from the mass of the measurement sample (Wa+Wb+Wc) is calculated and regarded as the sizing agent mass Wc of the sizing agent 15 applied to the measurement sample. (7) Based on the CF mass Wa obtained in (5) and the sizing agent mass Wc obtained in (6), the sizing agent mass ratio Rm (=Wc / Wa)×100%) is calculated.
[0058] In addition, in the determination of the above-mentioned sizing agent mass ratio Rm, when the CF mass Wa is determined according to the catalog value of the carbon fiber 13 (precursor), the mass of the carbon fiber 13 (precursor) to which the anti-interweaving sizing agent is not attached is determined. The anti-interweaving sizing agent mentioned here is a sizing agent attached to the surface of the carbon fiber 13 (precursor) in order to prevent the carbon fibers 13 (precursor) from interweaving with each other, etc., and is different from the sizing agent 15. However, the mass of the anti-interweaving sizing agent is generally about 1 / 100 of the CF mass Wa of the carbon fiber 13. In this case, whether the anti-interweaving sizing agent is attached will not substantially affect the preferred range of the sizing agent mass ratio Rm. Therefore, in this case, the mass of the carbon fiber 13 to which the anti-interweaving sizing agent is attached can be regarded as the CF mass Wa when the sizing agent mass ratio Rm is calculated.
[0059] In addition, the determination of the CF mass Wa is not limited to determination from the catalog value. For example, the mass of the carbon fiber 13 after the CNT17 is separated can also be measured as the CF mass Wa. Furthermore, for carbon fibers of the same type as the carbon fibers 13 used in the composite fiber 11 as the measurement sample and without CNT17 attached, the CF mass Wa can also be determined based on the mass measurement results.
[0060] [Method for producing molded article] exist Figure 7 In the process, the molded body 10 is manufactured through a structure forming step ST1, a sizing step ST2, a post-curing step ST3, and an injection molding step ST4. The injection molding step ST4 includes a kneading step ST4a and an injection step ST4b.
[0061] In the structure forming step ST1, CNT17 is attached to each of the carbon fibers 13 (filaments) of the carbon fiber bundle to form a structure 14. In order to form the structure 14, the carbon fiber bundle is immersed in a CNT separation dispersion (hereinafter referred to as the dispersion) in which the CNT17 is separated and dispersed, and mechanical energy is applied to the dispersion. Separation dispersion refers to a state in which CNT17 is physically separated one by one and dispersed in a dispersion medium without being intertwined with each other, and refers to a state in which the proportion of an aggregate of two or more CNT17s gathered into a bundle is less than 10%. Here, if the proportion of the aggregate is more than 10%, the coagulation of CNT17 in the dispersion medium is promoted, and the adhesion of CNT17 to the carbon fiber 13 is hindered.
[0062] like Figure 8 As shown in the example of FIG. 1 , the attachment device 21 used in the structure forming step ST1 is composed of a CNT attachment tank 22, guide rollers 23 to 26, an ultrasonic generator 27, etc. A dispersion 28 is contained in the CNT attachment tank 22. The ultrasonic generator 27 applies ultrasonic waves to the dispersion 28 in the CNT attachment tank 22 from the lower side of the CNT attachment tank 22.
[0063] A thin and long (e.g., about 100 m) carbon fiber bundle 29 that has not formed the structure 14 is continuously supplied to the attachment device 21. The supplied carbon fiber bundle 29 is sequentially wound around guide rollers 23 to 26 and is moved at a constant speed by a moving mechanism (not shown). The carbon fiber bundle 29 to which the anti-interlacing sizing agent is not attached is supplied to the attachment device 21.
[0064] The carbon fiber bundles 29 are respectively wound around the guide rollers 23 to 26 in a fiber-opened state. The carbon fiber bundles 29 wound around the guide rollers 23 to 26 can reduce the possibility of the carbon fibers 13 being intertwined with each other by applying appropriate tension. The carbon fiber bundles 29 are preferably wound at a smaller winding angle (less than 90°) relative to the guide rollers 23 to 26.
[0065] The guide rollers 23 to 26 are all flat rollers. The roller length (axial length) of the guide roller 23 is sufficiently larger than the width of the carbon fiber bundle 29 after fiber opening. The guide rollers 24 to 26 are also similar to the guide roller 23, and their roller lengths are sufficiently larger than the width of the carbon fiber bundle 29 after fiber opening. For example, the guide rollers 23 to 26 are all of the same size, with a roller length of 100 mm and a roller diameter (outer diameter) of 50 mm. The carbon fiber bundle 29 after fiber opening has a plurality of carbon fibers 13 arranged in the thickness direction (radial direction of the guide roller).
[0066] The guide rollers 24 and 25 of the guide rollers 23 to 26 are arranged in the CNT attachment groove 22. Thus, between the guide rollers 24 and 25, the carbon fiber bundle 29 travels straightly at a certain depth in the dispersion 28. The travel speed of the carbon fiber bundle 29 is preferably in the range of 0.5 m / min or more and 100 m / min or less. The higher the travel speed of the carbon fiber bundle 29, the more productivity can be improved, and the lower the travel speed, the more effective it is for uniform adhesion of CNT17 and the more effective it is for suppressing the interweaving of carbon fibers 13. In addition, the less interweaving of carbon fibers 13, the more uniform the adhesion of CNT17 to carbon fibers 13 can be improved. If the travel speed of the carbon fiber bundle 29 is 100 m / min or less, the interweaving of carbon fibers 13 can be more effectively suppressed, and the uniformity of adhesion of CNT17 can be further improved. In addition, the travel speed of the carbon fiber bundle 29 is more preferably in the range of 5 m / min or more and 50 m / min or less.
[0067] The ultrasonic generator 27 applies ultrasonic vibration as mechanical energy to the dispersion 28. As a result, a reversible reaction state in which the dispersed state of CNT17 is dispersed and the condensed state of CNT17 is alternately changed is formed in the dispersion 28. If the carbon fiber bundle 29 is passed through the dispersion 28 in the reversible reaction state, when the dispersion state is transferred to the condensed state, the CNT17 is attached to each carbon fiber 13 by the van der Waals force. The mass of carbon fiber 13 is more than 100,000 times greater than that of CNT17, and the energy used to separate the attached CNT17 becomes greater than the energy of ultrasonic vibration. Therefore, in the dispersion 28, once the CNT17 is attached to the carbon fiber 13, it will not be peeled off from the carbon fiber 13 even under the action of ultrasonic vibration after attachment. In addition, since the mass of CNT17 is extremely small, it is alternately changed to a dispersed state and a condensed state by ultrasonic vibration.
[0068] By repeatedly transferring from a dispersed state to an aggregated state, a plurality of CNTs 17 are attached to each carbon fiber 13 to form a structure 14. As described above, by using a curved CNT 17, other CNTs 17 enter the space formed between the CNT 17 and the surface of the carbon fiber 13 to which the CNT 17 is attached, or between the attached CNTs 17, so that more CNTs 17 are attached to the carbon fiber 13 to form a structure 14.
[0069] The frequency of the ultrasonic vibration applied to the dispersion 28 is preferably 40 kHz or more and 950 kHz or less. If the frequency is above 40 kHz, the interweaving of the carbon fibers 13 in the carbon fiber bundle 29 can be suppressed. In addition, if it is above 100 kHz, since the cavitation of the dispersion 28 is suppressed, the collision damage between the carbon fibers can be suppressed. If the frequency is below 950 kHz, the CNT 17 is well attached to the carbon fibers 13. In order to further reduce the mechanical damage or interweaving to the carbon fibers 13, the frequency of the ultrasonic vibration is preferably 100 kHz or more.
[0070] In addition, the inventors have found that the number of CNT17 attached to the carbon fiber 13 can be well suppressed from interweaving with each other by setting the number of transitions of CNT17 from a dispersed state to a cohesive state to be more than 100,000 times, and the uniformity of the thickness of the structure 14 can be ensured. In addition, the maximum value of the number of attached roots varies according to the CNT concentration of the dispersion 28, and the higher the CNT concentration of the dispersion 28, the greater the maximum value of the number of attached roots. However, if the CNT concentration of the dispersion 28 reaches a high concentration at which the CNT17 cannot be in a dispersed state when ultrasonic vibration is applied, the CNT17 cannot be attached to the carbon fiber 13.
[0071] Therefore, it is preferred that the length of the period during which the carbon fiber bundle 29 travels in the dispersion 28, that is, the time during which the carbon fiber bundle 29 travels between the guide rollers 24 and 25 (hereinafter referred to as the immersion time) is 100,000 times or more the period of the ultrasonic vibration applied to the dispersion 28, and the travel speed of the carbon fiber bundle 29, the distance the carbon fiber bundle 29 travels in the dispersion 28 (the interval between the guide rollers 24 and 25), and the frequency of the ultrasonic vibration applied to the dispersion 28 are determined. That is, when the frequency of the ultrasonic vibration is fs (Hz) and the immersion time is Ts (seconds), it is preferred to satisfy "Ts ≥ 100000 / fs". For example, if the frequency of the ultrasonic vibration is 100 kHz and the distance the carbon fiber bundle 29 travels in the dispersion 28 is 0.1 m, the travel speed of the carbon fiber bundle 29 may be 6 m / min or less. Even when carbon fiber bundle 29 is immersed in dispersion liquid 28 for a plurality of times, the number of attached CNTs 17 can be substantially maximized if the total immersion time is 100,000 times or more the period of ultrasonic vibration.
[0072] The ultrasonic vibration applied from the ultrasonic generator 27 generates a standing wave with a determined sound pressure (amplitude) distribution in the dispersion 28 in the CNT attachment tank 22. In the attachment device 21, the positions of the guide rollers 24 and 25 in the depth direction are adjusted so that the carbon fiber bundle 29 in the dispersion 28 travels at a node of the standing wave of the ultrasonic vibration, that is, at a depth where the sound pressure is extremely low. Therefore, the depth of the carbon fiber bundle 29 from the liquid surface of the dispersion 28 when traveling in the dispersion 28 is determined as follows: the depth is set to D P , when the wavelength of the standing wave of ultrasonic vibration generated in the dispersion 28 is λ and n is an integer greater than 1, "D P =n·(λ / 2)”. In addition, the wavelength λ of the standing wave can be obtained from the sound velocity in the dispersion 28 and the frequency of the ultrasonic vibration applied from the ultrasonic generator 27.
[0073] As described above, by adjusting the travel depth of the carbon fiber bundle 29 traveling in the dispersion 28, the vibration of the carbon fiber 13 caused by the sound pressure can be suppressed, and the fiber disorder caused by fiber relaxation can be prevented. The friction between the carbon fibers 13 or between the CNTs 17 attached to the surface of each carbon fiber 13 can be suppressed, and a structure 14 with a larger thickness can be formed. In addition, by suppressing the friction, even if the thickness of the structure 14 increases, the deviation of the CNT mass ratio Rc is suppressed, and the above-mentioned standard deviation s becomes smaller. In addition, the depth of the carbon fiber bundle 29 traveling in the dispersion 28 can be slightly deviated from the node of the standing wave. In this case, it is preferably within the range of n·λ / 2-λ / 8 or more and n·λ / 2+λ / 8 or less (n·λ / 2-λ / 8≤D P ≤n·λ / 2+λ / 8). Thus, the fiber disorder of the carbon fibers 13 due to fiber relaxation can be kept within an allowable range.
[0074] For example, by adding elongated CNTs (hereinafter referred to as material CNTs) into a dispersion medium, cutting the material CNTs using a homogenizer, shear force, ultrasonic disperser, etc., CNTs 17 of a desired length are obtained, and the dispersion 28 is prepared by achieving uniform dispersion of CNTs 17.
[0075] As the dispersion medium, water, alcohols such as ethanol, methanol, and isopropanol, or organic solvents such as toluene, acetone, tetrahydrofuran (THF), methyl ethyl ketone (MEK), hexane, n-hexane, ether, xylene, methyl acetate, and ethyl acetate, and mixtures thereof in any proportions can be used. The dispersion 28 does not contain a dispersant or a binder.
[0076] As described above, the material CNTs that form the basis of the curved CNT 17 are curved in shape. Such material CNTs preferably have the same diameter for each material CNT. The material CNTs are preferably a material that can separate and disperse the CNTs even if the length of each CNT generated by cutting is large. Thus, it is easy to obtain a dispersion 28 of CNTs 17 that are separated and dispersed to meet the above-mentioned length conditions.
[0077] In the composite fiber 11 of this example, as described above, since the CNT 17 of the curved shape is attached, other CNT 17 enters the space formed between the CNT 17 and the surface of the carbon fiber 13 to which the CNT 17 is attached, or the space formed between the attached CNT 17. As a result, more CNT 17 is attached to the carbon fiber 13. In addition, since the CNT 17 is firmly attached to the carbon fiber 13 to form the structure 14, it is more difficult for the CNT 17 to be peeled off from the carbon fiber 13. Moreover, the molded body 10 made using such a composite fiber 11 has higher properties derived from the CNT 17.
[0078] The concentration of CNT 17 in dispersion liquid 28 is preferably in the range of 0.003 wt % to 3 wt %. The concentration of CNT 17 in dispersion liquid 28 is more preferably in the range of 0.005 wt % to 0.5 wt %.
[0079] In the structure forming step ST1, the dispersion medium adhering to the carbon fiber bundle 29 drawn out from the dispersion liquid 28 is evaporated and dried. After the structure forming step ST1, the dried carbon fiber bundle 29 is subjected to a sizing treatment step ST2.
[0080] The sizing treatment step ST2 performs a sizing treatment of imparting a sizing agent 15 to the structure 14. The sizing treatment includes imparting a sizing treatment liquid to the carbon fiber bundle 29 formed with the structure 14 (making it contact) and a drying treatment to dry it. The sizing treatment liquid can be prepared by dissolving a raw material (compound) (in this example, the above-mentioned carbodiimide compound) in a solvent. The solvent used for dissolving can be appropriately selected. For example, as a solvent for dissolving the carbodiimide compound, water, alcohol, ketones and mixtures thereof can be used.
[0081] The sizing treatment liquid can be applied by any method such as immersing the carbon fiber bundle 29 in a liquid tank containing the sizing treatment liquid, spraying the sizing treatment liquid on the carbon fiber bundle 29, or applying the sizing treatment liquid on the carbon fiber bundle 29. The sizing treatment liquid is applied to the surface of the CNT 17 while maintaining direct contact between the CNTs 17. The lower the viscosity, the easier it is to condense near the contact portion between the CNTs 17 and the contact portion between the carbon fiber 13 and the CNT 17.
[0082] In the sizing treatment step ST2 , a desired sizing agent mass ratio Rm can be achieved by adjusting the amount of sizing treatment liquid applied to the carbon fiber bundle 29 , the raw material concentration of the sizing agent in the sizing treatment liquid, and the like.
[0083] In the drying process after the sizing treatment liquid is applied, the solvent (water in this example) of the sizing treatment liquid is evaporated to form a sizing agent 15 that cross-links the contact portions between CNTs 17 and the contact portions between CNTs 17 and carbon fibers 13. Thus, a composite fiber bundle 12 composed of a plurality of composite fibers 11 is obtained. The drying method can be achieved by a known drying method such as a method of placing and drying the carbon fiber bundle 29 to which the sizing treatment liquid has been applied, a method of conveying a gas such as air to the carbon fiber bundle 29, and a method of heating the carbon fiber bundle 29. A heating method can also be used in combination with any of the methods of placing and drying or conveying a gas.
[0084] In the post-curing step ST3 after the sizing step ST2, the sizing agent 15 is cured and the strength of the sizing agent 15 is improved. As a result, when the molded body 10 is produced, the disintegration of the structure 14 and the peeling from the carbon fiber 13 can be more effectively suppressed. In addition, the post-curing in the post-curing step ST3 does not require active heating, and the sizing agent 15 can be cured at room temperature, for example.
[0085] In this example, in the post-curing process ST3, the composite fiber bundle 12 that has undergone the sizing process ST2 is set to a predetermined post-curing temperature, and the post-curing temperature is maintained only during the post-curing period corresponding to the post-curing temperature to perform post-curing. For example, post-curing is performed by placing the composite fiber bundle 12 in an atmosphere that reaches the post-curing temperature. As long as the various substances constituting the composite fiber 11 do not deteriorate, the post-curing temperature and the post-curing period can be set arbitrarily, but according to the Arrhenius' equation, the lower the post-curing temperature, the longer the post-curing period is set. In this example, the post-curing temperature is kept constant. For example, when the post-curing temperature is 70°C, the post-curing period is set to 0.5 days (12 hours), and at a lower temperature of 20°C, the post-curing period is set to a longer 16 days (384 hours).
[0086] Here, it was confirmed that when the post-curing temperature is set to T (°C) and the post-curing period is set to D (days), if the post-curing is performed in a manner that satisfies "T ≥ 14.43ln (D) + 60", the disintegration of the structure 14 and the peeling from the carbon fiber 13 are preferably suppressed. Fig. 9 In the diagram shown in FIG. 1 , the post-curing temperature and the post-curing period are preferably determined in such a manner that the post-curing temperature and the post-curing period are within the region indicated by the hatched line on the curve of the formula "T = 14.43ln (D) + 60" indicated by the symbol Eq and above the curve Eq. Fig. 9 In the figure, the range of the post-curing temperature is 0°C to 80°C, but the range of the post-curing temperature is not limited thereto. In addition, when a compound other than the carbodiimide compound is used to impart the sizing agent as described above, post-curing is also preferably performed, and in this case, the relationship between the post-curing temperature T and the post-curing period D as described above is preferably satisfied.
[0087] When post-curing is performed at a minimum post-curing period relative to a post-curing temperature, the relationship "T = 14.43ln(D) + 60" can be satisfied. In this case, for example, when the post-curing temperature is 70°C, 60°C, 50°C, 40°C, 30°C, 20°C, 10°C, and 0°C, the post-curing period can be set to 0.5 days, 1 day, 2 days, 4 days, 8 days, 16 days, 32 days, and 64 days in this order.
[0088] In addition, during post-curing, when the post-curing temperature is changed to a lower temperature during the process, the post-curing period can be set longer accordingly, and when the post-curing temperature is changed to a higher temperature during the process, the post-curing period can be shortened accordingly.
[0089] In the injection molding step ST4, the composite fiber bundle 12 that has undergone the post-curing step ST3 is used to produce the molded body 10 by injection molding. As described above, the injection molding step ST4 includes a kneading step ST4a and an injection step ST4b. In the kneading step ST4a, a molten thermoplastic resin (hereinafter referred to as a molten resin) and a composite fiber 11 are kneaded so that the composite fiber 11 is dispersedly contained in the molten resin. In the injection step ST4b, the molded body 10 is injection molded by injecting the molten resin containing the composite fiber 11 generated in the kneading step ST4a into a metal mold.
[0090] In the production of the molded body 10, an injection molding machine is used. The injection molding machine is composed of an injection device and a clamping device, etc. The injection device injects molten resin of the thermoplastic resin that is heated and melted to form the matrix resin M into the metal mold, and the clamping device resists the opening and closing of the metal mold and the pressure of the molten resin injected into the metal mold, so as to keep the metal mold in a closed state.
[0091] In this example, a screw preplunger-type injection molding device having an injection device having a plasticizing unit and an injection unit is used. The plasticizing unit mixes the molten resin obtained by heating and melting the thermoplastic resin and the reinforcing fiber (composite fiber 11 in this example) in the plasticizing barrel. The injection unit supplies the molten resin containing the composite fiber 11 from the plasticizing unit into the injection barrel. When a certain amount of molten resin is supplied, the molten resin in the injection barrel is injected into the metal mold by the plunger, and the molten resin containing the composite fiber 11 is filled into the metal mold. After a cooling process, the metal mold is opened and the molded body 10 is taken out. Therefore, the plasticizing unit is used in the mixing process ST4a, and the injection unit, the metal mold and the mold clamping device are used.
[0092] In addition, the injection molding device used in this example is an injection molding device of the LFT-D (Long Fiber Thermoplastics-Direct, long fiber online compression molding) method, and the slender composite fiber bundle 12 is continuously supplied to the plasticizing barrel from a creel or the like. For example, the composite fiber bundle 12 is introduced into the plasticizing barrel by the rotation of a screw for mixing molten resin. Each composite fiber 11 of the composite fiber bundle 12 is sandwiched between the spiral blades of the screw and the inner surface of the barrel, and is sheared to an appropriate length by the stress from the molten resin in mixing, and is dispersed in the molten resin through mixing. The mixing conditions such as pressure and temperature in the plasticizing unit can be set to conditions suitable for the resin material that becomes the matrix resin M.
[0093] The molten resin in the kneading in the plasticizing unit has a high viscosity, and a large stress acts on the structure 14, which causes the structure 14 to peel off from the carbon fiber 13 or the structure 14 to disintegrate. However, in this example, as described above, since the sizing agent 15 is used to firmly fix the CNTs 17 to each other and the carbon fiber 13 to the CNTs 17, it is not easy to peel off or disintegrate the structure 14 even if a large stress acts during kneading. In addition, since the sizing agent 15 is applied to the structure 14, it is even more difficult for the structure 14 to peel off or disintegrate, and since the strength of the sizing agent 15 is increased after the post-curing step ST3, it is even more difficult for the structure 14 to peel off or disintegrate.
[0094] In addition, the composite fiber 11 and the pellets of the resin material which are cut into appropriate lengths in advance, or the pellets containing the composite fiber 11 which are cut into appropriate lengths in the resin material can be supplied to the plasticizing barrel to produce the molded body 10, but in this case, the composite fiber 11 is also sheared in the plasticizing barrel. On the other hand, from the viewpoint of improving the mechanical strength of the molded body 10, it is advantageous that the reinforcing fibers in the molded body 10 are longer. As shown in this example, the elongated composite fiber bundle 12 is directly supplied to the plasticizing barrel, so that the composite fiber 11 in the molded body 10 is longer, which is beneficial to improving the mechanical strength of the molded body 10. The injection molding machine used when producing such a molded body 10 is not limited to the screw pre-plunger type injection molding machine, and various types of injection molding machines can be used.
[0095] It was confirmed that the fiber volume content (Vf) of the composite fiber 11 of the molded body 10 has a positive correlation with the tensile strength, which is one of the mechanical strengths. From the viewpoint of improving the tensile strength, a higher fiber volume content is preferred. On the other hand, it was confirmed that the effect of suppressing the deviation of the tensile strength of the molded body 10 becomes significant by making the fiber volume content 27% or more. From such a viewpoint, it is preferred to make the fiber volume content 27% or more. As a molded body 10, if the fiber volume content is 27% or more, the tensile strength is indeed high. In addition, the fiber volume content (Vf) of the composite fiber 11 of the molded body 10 can be adjusted by increasing or decreasing the rotation speed of the screw, etc.
[0096] The fiber volume content (Vf) of the composite fibers 11 in the molded body 10 is determined from the formula (3) by burning the molded body 10 and using the masses before and after the burning.
[0097] [Mathematical formula 2]
[0098] The value W in formula (3) S is the mass of the molded body 10 before combustion, and the value W CFis the mass of the residue obtained after removing the matrix resin M from the molded body 10 by combustion, and the value d R is the specific gravity of the matrix resin M, value d CF is the specific gravity of the carbon fiber 13. In this example, the volume and weight of the CNT 17 and the sizing agent 15 in the composite fiber 11 are very small compared to the carbon fiber 13, so the specific gravity of the carbon fiber 13 is d CF The fiber volume content of the conjugate fiber 11 was determined by taking it as the specific gravity of the conjugate fiber 11. The fiber volume content by the combustion method is measured in accordance with JIS K 7075-1991.
[0099] Specific gravity of carbon fiber 13 CF The value measured by a measuring instrument (for example, a high-precision electronic densitometer SD-200L (manufactured by ALFAMIRAGE Co., Ltd., Japan) is used, but a catalog value (a nominal value of the manufacturer of the carbon fiber 13) may also be used. The specific gravity d of the matrix resin M R The value measured by the measuring instrument is used.
[0100] The molded body 10 is produced as described above, in which the matrix resin M enters the voids 19 of the structure 14 and solidifies. Therefore, the molded body 10 is less likely to be peeled off from the carbon fibers 13 or the composite fibers 11 and the matrix resin M due to the anchoring effect of the structure 14 and the relaxation of stress concentration, and the mechanical strength such as tensile strength is improved.
[0101] Alternatively, the molded body 10 obtained by injection molding as described above may be used as a primary molded body, and the primary molded body may be further molded to produce a secondary molded body. For example, the primary molded body may be made into a flat plate, and the primary molded body may be stamped to produce a secondary molded body of a desired shape.
[0102] Not limited to the injection-molded article produced as described above, the composite fibers in the matrix resin can be easily recycled (recycled). Fig.10 The product 31 manufactured in the manufacturing step ST11 is a resin containing the composite fiber 11, and the product 31 includes a molded body (carbon fiber reinforced plastic) using the composite fiber 11 as a reinforcing fiber, a prepreg as an intermediate material for manufacturing the molded body, and the like.
[0103] In the manufacturing process ST11, for example, when the product 31 is a prepreg, it is a process of manufacturing the prepreg from the resin that becomes the matrix resin of the molded body and the composite fiber 11. When manufacturing a molded body, it is a molding process corresponding to the manufacturing method of the molded body. The manufacturing method of the molded body as the product 31 is not limited, and examples thereof include: injection molding as described above, stamping molding using prepreg, autoclave molding, bag molding, sheet winding molding and internal pressure molding, hand lay-up molding without using prepreg, filament winding molding, drawing molding, etc.
[0104] In the recycling step ST12, the prepreg or molded product scraps generated in the molded product manufacturing step ST11, scraps generated in the prepreg manufacturing step, and unnecessary molded products are recycled as a composite 32. The composite 32 is a composite in which the composite fiber 11 and the resin are integrated. The composite 32 has a form in which the composite fiber 11 is contained in the resin, or a form in which the resin is partially attached to the composite fiber 11, similarly to the prepreg or the molded product. In this example, the recycling step ST12 is a preparation step.
[0105] The resin of the recovered composite 32 is removed by the removal step ST13. The removal of the resin is carried out, for example, by heating the composite 32 to a high temperature (e.g., 500° C.) in a furnace to thermally decompose or burn the resin. In addition, the heating temperature of the composite 32 is determined to be a temperature at which the resin can be thermally decomposed or burned, and the carbon fibers 13 of the composite fiber 11 and the structure 14 on its surface can remain. At this time, the sizing agent 15 given to the structure 14 may be removed together with the resin by thermal decomposition or combustion, or may not be removed. Thus, as a product, a CNT-attached carbon fiber 33 consisting of the carbon fiber 13 and the carbon fiber 13 having the structure 14 on its surface is obtained. In addition, the CNT-attached carbon fiber 33 obtained in this way may also be washed. In addition, the removal of the resin in the removal step ST13 is not limited to thermal decomposition or combustion, and may also be a dissolution method using an organic solvent or an acid or alkali.
[0106] In the composite material manufacturing step ST14, the CNT-attached carbon fiber 33 obtained in the removal step ST13 is used as a reinforcing fiber to manufacture a carbon fiber composite material 34. That is, a carbon fiber composite material 34 is manufactured in which the CNT-attached carbon fiber 33 is embedded in a resin (matrix resin). The carbon fiber composite material 34 is a molded body or a prepreg produced by the above-mentioned various methods. The resin used in the composite material manufacturing step ST14 can be a resin corresponding to the carbon fiber composite material 34 to be manufactured or its manufacturing method.
[0107] For example, carbon fibers obtained by heating a molded body to a high temperature to remove the resin have a reduced bonding strength with the matrix resin due to the inactivation of the surface. Therefore, when using the carbon fibers to make carbon fiber composite materials, the carbon fibers need to be surface treated to increase the bonding strength with the matrix resin.
[0108] In contrast, the CNT-attached carbon fiber 33 forms a structure 14 on the surface of the carbon fiber 13. As described above, the matrix resin enters the voids 19 of the structure 14 and solidifies. Therefore, even without surface treatment, a high bonding strength can be obtained between the CNT-attached carbon fiber 33 and the matrix resin. As a result, a molded body with high mechanical strength can be produced. In addition, when the CNT-attached carbon fiber 33 is used in the above-mentioned injection molding, when the sizing agent is removed, the structure 14 may partially fall off during the mixing of the thermoplastic resin. However, by the structure 14 remaining on the surface of the carbon fiber 13, an injection molded body with high mechanical strength can be produced.
[0109] In the above description, an example of a product containing composite fibers obtained by imparting a sizing agent to a structure as a reinforcing fiber is described, but a product may contain carbon fibers having a structure not imparted with a sizing agent provided on the surface as a reinforcing fiber instead of the composite fiber 11. Example
[0110] [Example 1] In Example 1, sample fibers A11 and A12 of composite fiber 11 were prepared according to the above procedure, and a peeling test of CNT 17 was conducted to confirm the effect of sizing agent 15. Dispersion liquid 28 used in preparing composite fiber 11 was prepared using material CNT having the above-mentioned curved shape. Fig.11 The SEM photograph of the material CNT used to prepare the dispersion 28 is shown. The material CNT is multilayered and has a diameter in the range of 3 nm or more and 10 nm or less. The material CNT is washed with a 3:1 mixed acid of sulfuric acid and nitric acid, and after removing the catalyst residue, it is filtered and dried. The material CNT is added to acetone as the dispersion medium of the dispersion 28, and the material CNT is cut using an ultrasonic homogenizer to make CNT17. The length of CNT17 in the dispersion 28 is greater than 0.2 μm and less than 5 μm. In addition, the CNT17 in the dispersion 28 is CNT17 that can be evaluated as a curved shape. The concentration of CNT17 in the dispersion 28 is 0.12wt% (=1200wt ppm). No dispersant or adhesive is added to the dispersion 28.
[0111] As the carbon fiber bundle 29, TORAYCA (registered trademark) T700SC-12000 (manufactured by Toray Industries, Ltd., Japan) is used. The carbon fiber bundle 29 contains 12,000 carbon fibers 13. The diameter of the carbon fiber 13 is about 7 μm and the length is about 500 m. In addition, the carbon fiber bundle 29 removes the anti-interweaving sizing agent of the carbon fiber 13 from the surface of the carbon fiber 13 before the attachment of the CNT 17.
[0112] The carbon fiber bundle 29 is wound around the guide rollers 23 to 26 in an open state, and is made to travel in the dispersion 28 in the CNT attachment tank 22. The travel speed of the carbon fiber bundle 29 is 1 m / min, and ultrasonic vibrations with a frequency of 200 kHz are applied to the dispersion 28 by the ultrasonic generator 27. In addition, the immersion time between the guide rollers 24 and 25 is 6.25 seconds. The immersion time is the time of 1250000 cycles of ultrasonic vibrations provided to the dispersion 28. In the dispersion 28, the carbon fiber bundle 29 is made to travel at a distance satisfying "D P =n·(λ / 2)" The depth D of the liquid surface of the dispersion liquid 28 P Moving forward.
[0113] After the carbon fiber bundle 29 drawn out from the dispersion 28 is dried, a sizing treatment is performed to obtain a composite fiber bundle 12 in which the sizing agent 15 is applied to the CNTs 17 constituting the structure 14 .
[0114] In the sizing treatment of the sample fiber A11, a sizing treatment liquid obtained by dissolving "CARBODILITE V-02" (trade name, manufactured by Nisshinbo Chemical Co., Ltd., Japan) in water was used as a carbodiimide compound. In addition, in the sizing treatment of the sample fiber A12, a sizing treatment liquid obtained by dissolving an epoxy resin in acetone was used. The concentrations of the carbodiimide compound and the epoxy resin in the sizing treatment liquid were adjusted so that the sizing agent mass ratio Rm was 1.0%. After applying the sizing treatment liquid, the water as a solvent was evaporated to dry the composite fiber bundle 12.
[0115] A portion of the composite fiber bundle 12 to which the sizing treatment was applied as described above was cut out, and the obtained plurality of composite fibers 11 were used as sample fibers A11 and A12. It was observed by SEM that a plurality of CNTs 17 were uniformly dispersed and attached to the sample fibers A11 and A12. As a result, it was confirmed that in the sample fibers A11 and A12, CNTs 17 were uniformly attached in a narrow range (local) and a wide range in the fiber axis direction of the carbon fiber 13 to form a structure 14. In addition, the structure 14 was formed into a three-dimensional grid-like structure composed of a plurality of CNTs 17, that is, a non-woven fabric having a void portion 19, and it was confirmed that most of the void portion 19 was not blocked by the sizing agent 15. In addition, post-curing was not performed in this Example 1.
[0116] In the CNT17 peeling experiment, sample fibers A11 and A12 were immersed in a mixture of water and surfactant in different containers, and ultrasonic vibrations were applied to the mixture for 10 minutes by an ultrasonic generator. The length of the sample fiber immersed in the mixture was 1m, the concentration of the surfactant in the mixture was 0.2% by mass, and the frequency of the ultrasonic vibrations applied to the mixture was 100kHz.
[0117] In the peeling test of sample fiber A11, it was confirmed that the mixed solution was slightly turbid and CNT17 hardly fell off from carbon fiber 13. In the peeling test of sample fiber A12, the mixed solution became black and turbid, but when it was confirmed after the peeling test, it was confirmed that CNT17 had not fallen off from carbon fiber 13. That is, it can be seen that the sizing agent 15 having a carbodiimide-derived structure makes the contact between CNT17 and CNT17 and carbon fiber 13 more firm, and can more effectively suppress the disintegration of structure 14 and the peeling of structure 14 from carbon fiber 13, so it is particularly preferred.
[0118] [Example 2] In Example 2, a plurality of test pieces A21 to A23 having different fiber volume contents were prepared as molded products 10 using composite fibers 11 as reinforcing fibers, and fiber volume contents were measured and tensile tests were performed.
[0119] Using a screw pre-plunger injection molding machine (L Former100-AP, manufactured by Toshiba Machine Co., Ltd., Japan), the elongated composite fiber bundle 12 was continuously supplied to the plasticizing barrel to produce test pieces A21 to A23. The composite fiber bundle 12 was produced under the same conditions as the sample fiber A11 of Example 1, but a composite fiber bundle that had been post-cured was used in this Example 2. The post-curing temperature was 60°C, and the post-curing time was 1 day. As the thermoplastic resin of the matrix resin M, MX-Nylon (trade name, manufactured by Mitsubishi Gas Chemical Co., Ltd., Japan) was used. Test pieces A21 to A23 were produced in the order of the fiber volume content of the composite fiber 11 being approximately 20%, 24%, and 27%. The shapes and dimensions of the test pieces A21 to A23 were made into A-shaped dumbbell shapes in accordance with ISO3167:2002.
[0120] In addition, as comparative example 1, the precursor (carbon fiber) was used as the reinforcing fiber, and a plurality of test pieces B21 to B23 were prepared, each of which had a fiber volume content of carbon fiber substantially the same as that of the test pieces A21 to A23, and the tensile strength of each test piece was measured in the same manner. Test pieces B21 to B23 were prepared in the same manner as test pieces A21 to A23. Any of the test pieces A21 to A23 and B21 to B23 used TORAYCA T700SC-12000 (manufactured by Toray Industries, Ltd.) as the carbon fiber 13.
[0121] A portion of each of the prepared test pieces A21 to A23 and test pieces B21 to B23 was used to measure the fiber volume content. The fiber volume content was determined by a combustion method. The combustion of the test piece was carried out by raising the temperature from room temperature to 450°C within 2 hours, and then maintaining it at 450°C for 10 hours, thereby completely removing the matrix resin M. As a result, the average values of the fiber volume contents of the test pieces A21 to A23 were 20.39%, 24.48%, and 27.32%, respectively, and the samples of the test piece A23 were all above 27%. In addition, the average values of the fiber volume contents of the test pieces B21 to B23 were 20.82%, 26.08%, and 28.29%, respectively.
[0122] The tensile test was conducted in accordance with JIS K7161: 2014, and the tensile strength (maximum tensile stress) of the test pieces A21 to A23 was measured. The tensile test was conducted at a tensile speed (test speed) of 5 mm / min.
[0123] Fig.12 The tensile strength of Example 2 and Comparative Example 1 obtained by tensile test is shown in FIG. Fig.13 Indicates the maximum load (maximum test force) corresponding to the tensile strength. Fig.14 Indicates the displacement of the test piece at the maximum load. Figure 12 to Figure 14 In the table, the average values of the test pieces A21 to A23 and B21 to B23 are shown, and the error bars (Error bars) show the distribution range of the actual measured values.
[0124] Regarding the maximum tensile stress and the maximum load, the test piece A21 has an advantage of about 2% over the test piece B21, the test piece A22 has an advantage of about 10.4% over the test piece B22, and the test piece A23 has an advantage of about 11.1% over the test piece B23.
[0125] In addition, from the above measurement results, it can be seen that regarding the maximum tensile stress and the maximum load, when the composite fiber 11 is used as the reinforcing fiber, there is a positive correlation between the fiber volume content and the tensile strength, and as the fiber volume content increases, the maximum tensile stress increases. In contrast, when the carbon fiber (precursor) is used as the reinforcing fiber, no positive correlation is found between the fiber volume content and the tensile strength. It can be further seen that when the composite fiber 11 is used as the reinforcing fiber, when its fiber volume content is 27% (or more), the deviation of the maximum tensile stress and the maximum load becomes very small. In contrast, it can be seen that when the carbon fiber (precursor) is used as the reinforcing fiber, when the fiber volume content increases, the deviation of the maximum tensile stress and the maximum load increases.
[0126] It can be seen that when carbon fibers (precursor fibers) are used as reinforcing fibers, the displacement at the maximum load tends to decrease as the fiber volume content increases, but when composite fibers 11 are used as reinforcing fibers, the displacement at the maximum load is not affected by the fiber volume content and hardly changes. In addition, it can be seen that when composite fibers 11 are used as reinforcing fibers, as the fiber volume content increases, the deviation of the displacement at the maximum load decreases, and when the fiber volume content is 27% (or more), the deviation of the displacement at the maximum load is very small.
[0127] [Example 3] As Example 3, PA66 (nylon-66) was used as a thermoplastic resin forming the matrix resin M, and as a molded body 10 using the composite fiber 11 as a reinforcing fiber, a plurality of test pieces A31 and A32 having different fiber volume contents were prepared. In addition, as Comparative Example 2, PA66 was used as a thermoplastic resin, and test pieces B31 and B32 using carbon fibers (precursors) as reinforcing fibers were prepared. For these test pieces A31, A32 and test pieces B31, B32, the fiber volume contents were measured and the tensile test was performed in the same manner as in Example 2.
[0128] The test pieces A31 and B31 were made to have a fiber volume content of about 20%, and the test pieces A32 and B32 were made to have a fiber volume content of about 24%. In addition, the other production conditions of the test pieces A31, A32, test pieces B31, and B32 were the same as those in Example 2. The fiber volume content was obtained by the combustion method using a portion of each of the test pieces A31, A32, B31, and B32. Regarding the fiber volume content, the test piece A31 was 19.5%, the test piece A32 was 24.0%, the test piece B31 was 19.4%, and the test piece B32 was 23.6%.
[0129] Fig.15 The tensile strength of Example 3 and Comparative Example 2 obtained by tensile test is shown in FIG. Fig.16 Indicates the displacement of the test piece at the maximum load. Fig.15 , Fig.16 The measurement results of the test piece C31 made of the matrix resin M composed of PA66 without reinforcing fibers are also shown. Fig.15 , Fig.16 In FIG. 1 , the average values of the test pieces A31, A32, B31, B32, and C31 are shown.
[0130] Depend on Fig.15It can be seen that the tensile strength of the test pieces A31, A32 and the test pieces B31, B32 containing reinforcing fibers is greatly improved compared to the test piece C31 containing only the matrix resin M, but the tensile strength of the test pieces A31 and A32 using the composite fiber 11 as the reinforcing fiber is also greater than that of the test pieces B31 and B32 using the carbon fiber as the reinforcing fiber (raw yarn). In addition, when the test pieces with approximately the same fiber volume content are compared with each other, the tensile strength of the test piece A31 with a fiber volume content of about 20% is increased by 5% relative to the test piece B31, and the tensile strength of the test piece A32 with a fiber volume content of about 24% is increased by 11% relative to the test piece B32.
[0131] Fig.17 The image of the fracture surface of the test piece A31 after the tensile test observed by a scanning electron microscope is shown. Fig.18 The image of the fracture surface of the test piece B31 after the tensile test is observed by a scanning electron microscope. In the test piece B31, the surface of the carbon fiber (precursor) as the reinforcing fiber is exposed, and it can be seen that the matrix resin M peels off at the interface of the carbon fiber (precursor) and becomes a damaged state, that is, interface damage occurs. In contrast, in the test piece A31, the surface of the composite fiber 11 is covered with the matrix resin M, and it can be seen that the destruction of the matrix resin M, that is, cohesive damage, occurs. It can be seen that the anchoring effect of the structure 14 and the relaxation of stress concentration make it difficult for the carbon fiber 13 or the composite fiber 11 to peel off from the matrix resin M, and the composite fiber 11 further improves the tensile strength of the molded body 10.
[0132] Fig.19 The figure shows an image of the surface of the composite fiber 11 in the residue obtained by burning and removing the matrix resin M of the test piece A31, observed by a field emission scanning electron microscope (FE-SEM). From this image, it can be confirmed that in the production of the molded body 10, even if kneading is performed by an injection molding machine, the structure 14 is not peeled off in the composite fiber 11 and remains on the surface of the carbon fiber 13. In addition, since there is no residue of the matrix resin M left on the surface of the composite fiber 11, it can be recycled in its original state, and the recycling process can be simplified, which is advantageous. Description of Reference Numerals
[0133] 10: Molded body; 11: composite fiber; 13: Carbon fiber; 14: structure; 15: sizing agent; 17: Carbon nanotubes; M: matrix resin.
Claims
1. An injection molded body, characterized in that: include: A plurality of composite fibers, comprising carbon fibers, a structure and a sizing agent, wherein the structure is composed of a plurality of carbon nanotubes having a bent shape with a bent portion, forming a network structure having a contact portion where the carbon nanotubes are in direct contact with each other, the structure is disposed on the surface of the carbon fibers, the sizing agent is disposed at least around the contact portion, and the carbon nanotubes in direct contact are cross-linked with each other via a structure obtained by reaction with functional groups of the carbon nanotubes; as well as The matrix resin embeds the plurality of composite fibers and is formed of a thermoplastic resin.
2. The injection molded body according to claim 1, characterized in that The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through a carbodiimide-derived structure obtained by reacting the functional groups of the carbon nanotubes with the carbodiimide groups.
3. The injection molded article according to claim 1, wherein: The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through an isocyanate-derived structure obtained by the reaction of the functional groups of the carbon nanotubes with the isocyanate groups.
4. The injection molded body according to any one of claims 1 to 3, characterized in that The fiber volume content of the plurality of composite fibers is 27% or more.
5. The injection molded body according to any one of claims 1 to 3, characterized in that The thickness of the structure is within a range of 50 nm to 200 nm.
6. The injection molded body according to any one of claims 1 to 3, characterized in that The carbon fiber provided with the structure is a product obtained by removing the resin from a composite in which the carbon fiber provided with the structure and the resin are integrated.
7. A method for producing an injection molded body, characterized in that: have: A mixing step of mixing the composite fiber and the thermoplastic resin; and an injection step of injection-molding the thermoplastic resin containing the conjugate fiber to obtain an injection-molded body in which the conjugate fiber is embedded in a matrix resin formed of the thermoplastic resin; The composite fiber comprises carbon fiber, a structure and a sizing agent, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion, forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other, the structure is arranged on the surface of the carbon fiber, the sizing agent is arranged at least around the contact portion, and the carbon nanotubes in direct contact are cross-linked with each other via a structure obtained by reaction with functional groups of the carbon nanotubes.
8. The method for producing an injection molded body according to claim 7, wherein: The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through a carbodiimide-derived structure obtained by reacting the functional groups of the carbon nanotubes with the carbodiimide groups.
9. The method for producing an injection molded body according to claim 7, wherein: The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through an isocyanate-derived structure obtained by the reaction of the functional groups of the carbon nanotubes with the isocyanate groups.
10. The method for producing an injection molded body according to any one of claims 7 to 9, characterized in that: In the kneading step, the elongated conjugate fibers are continuously supplied and cut.
11. The method for producing an injection molded body according to any one of claims 7 to 9, characterized in that: In the kneading step, the ratio of the thermoplastic resin to the conjugate fiber is adjusted so that the fiber volume content of the conjugate fiber in the injection molded article is 27% or more.
12. The method for producing an injection molded body according to any one of claims 7 to 9, characterized in that: have: The removing step removes the resin of the composite in which the carbon fibers and the resin are integrated and provided with the structure, thereby obtaining the carbon fibers and the structure as the composite fibers.
13. The method for producing an injection molded body according to any one of claims 7 to 9, characterized in that: Before the mixing step, there are: The post-curing step is to post-cure the sizing agent of the composite fiber.
14. The method for producing an injection molded body according to claim 13, wherein: In the post-curing step, when the post-curing temperature of the composite fiber is T and the post-curing period during which the post-curing temperature is maintained is D, "T≥14.43ln(D)+60" is satisfied, where T is in degrees Celsius and D is in days.
15. A method for producing a composite fiber, characterized in that: have: a structure forming step of forming a structure on the surface of the carbon fiber, wherein the structure is composed of a plurality of carbon nanotubes having a bent shape with a bent portion and forming a network structure having a contact portion where the carbon nanotubes are in direct contact with each other; A sizing treatment step, wherein the carbon fibers forming the structure are brought into contact with a sizing treatment liquid to impart a sizing agent to obtain a composite fiber, wherein the sizing treatment liquid dissolves a raw material of the sizing agent that cross-links the carbon nanotubes that are in direct contact with each other; as well as The post-curing step is to post-cure the sizing agent of the composite fiber.
16. The method for producing a composite fiber according to claim 15, characterized in that: In the post-curing step, when the post-curing temperature of the composite fiber is T and the post-curing period during which the post-curing temperature is maintained is D, "T≥14.43ln(D)+60" is satisfied, where T is in degrees Celsius and D is in days.
17. The method for producing a composite fiber according to claim 15 or 16, characterized in that: The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through a carbodiimide-derived structure obtained by the reaction of the functional groups of the carbon nanotubes with the carbodiimide groups.
18. The method for producing a composite fiber according to claim 15 or 16, characterized in that: The sizing agent cross-links the carbon nanotubes that are in direct contact with each other through an isocyanate-derived structure obtained by the reaction of the functional groups of the carbon nanotubes with the isocyanate groups.
19. A CNT-attached carbon fiber, characterized in that: The CNT-attached carbon fiber is a product obtained by removing the resin from a composite of carbon fiber and resin, wherein a structure is provided on the surface of the carbon fiber, the structure being composed of a plurality of carbon nanotubes having a curved shape with a curved portion and forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other.
20. A method for manufacturing CNT-attached carbon fiber, comprising: a preparation step of preparing a composite material in which carbon fibers and a resin are integrated and provided with a structure on the surface thereof, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion and forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other; and The removing step removes the resin of the composite to obtain CNT-attached carbon fibers.
21. A method for manufacturing a carbon fiber composite material, comprising: A preparation step of preparing a composite material in which a carbon fiber having a structure provided on the surface and a resin are integrated, wherein the structure is composed of a plurality of carbon nanotubes having a curved shape with a curved portion and forming a network structure having a contact portion in which the carbon nanotubes are in direct contact with each other; A removal step of removing the resin of the composite to obtain CNT-attached carbon fibers; as well as The composite material manufacturing step is to embed the CNT-attached carbon fiber in a matrix resin to obtain a carbon fiber composite material.
Citation Information
Patent Citations
Curing agent for aqueous resin and coating material using the same
JP2007238753A
Fiber-reinforced thermoplastic resin gear
JP2008008404A
Composite material, prepreg, carbon fiber reinforced molded product, and method for producing composite material
WO2019240094A1